3-Ketosteroid 9α-hydroxylase enzymes: Rieske non-heme monooxygenases essential for bacterial steroid degradation - Petrusma, Mirjan (Springer International Publishing, 2014)
Various micro-organisms are able to use sterols/steroids as carbon- and energy sources for growth. 3-Ketosteroid 9α-hydroxylase (KSH), a two component Rieske non-heme monooxygenase comprised of the oxygenase KshA and the reductase KshB, is a key-enzyme in bacterial steroid degradation. It initiates opening of the steroid polycyclic ring structure. The enzyme has industrial relevance in the synthesis of pharmaceutical steroids. Deletion of KSH activity in sterol degrading bacteria results in blockage of steroid ring opening and is used to produce valuable C19-steroids such as 4-androstene-3,17-dione and 1,4-androstadiene-3,17-dione. Interestingly, KSH activity is essential for the pathogenicity of Mycobacterium tuberculosis. Detailed information about KSH thus is of medical relevance, and KSH inhibitory compounds may find application in combatting tuberculosis. In recent years, the 3D structure of the KshA protein of M. tuberculosis H37Rv has been elucidated and various studies report biochemical characteristics and possible physiological roles of KSH. The current knowledge is reviewed here and forms a solid basis for further studies on this highly interesting enzyme. Future work may result in the construction of KSH mutants capable of production of specific bioactive steroids. Furthermore, KSH provides an promising target for drugs against the pathogenic agent M. tuberculosis.